The Determinants Of Non-Performing Financing In Sharia Banks In Indonesia, Oman, And The United Arab Emirates - Danty Priastarini Sabar; Falikhatun Falikhatun (Journal of Finance and Islamic Banking, 2022)
The increase in non-performing financing ratios occurred in several countries, such as Indonesia, Oman, and the United Arab Emirates from 2015 to 2019. The aim of this study is to determine the most influencing factors that caused NPF. Hence, the growth of NPF can be controlled once the most influencing factors of NPF are determined. The method used in this research is Multiple Linear Regression Analysis to examine the influence of Sale and Purchase contracts, Profit-Sharing Contracts, Financing to Deposit Ratio, and Financing Allowances on non-performing financing. This study was taken in Islamic Banks in Indonesia, Oman, and the United Arab Emirates. The results of this study indicated that Sale and Purchase Contracts, Profit-Sharing Contracts, and Financing Allowances have a significant effect on the NPF Ratio, while FDR did not affect NPF. Through this research, it is hoped that it can contribute to regulators implementing obligations that can control the rate of NPF.